Role of Axillary Ultrasound, Fine Needle Aspiration Cytology and Sentinel Lymph Node Biopsy in clinically N0 Breast Cancer - Goel, Gaurav (Indian J Surg Oncol, 2016)
This study evaluates the combined role of axillary ultrasound, fine needle aspiration cytology and sentinel lymph node biopsy in clinically N0 axilla. Between January 2014 and June 2015, 150 women with early breast cancer underwent axillary ultrasound as a first investigation for nodal status. Suspicious nodes were subjected to image guided fine needle aspiration cytology. Non-suspicious and fine needle aspiration cytology negative axillary nodes proceeded to sentinel lymph node biopsy at time of primary breast surgery. All confirmed positive (cytology and frozen) cases proceeded to axillary lymph node dissection. 52 women had positive axillary nodes at final histology. Axillary ultrasound with fine needle aspiration cytology identified 27 patients with positive axillary nodal status and had a sensitivity of 84.36 % (27/32) and specificity of 87.5 % (14/16). Intraoperative frozen analysis identified a further 13 cases with sensitivity of 56.52 % (13/23) and specificity of 97.56 % (80/82). Overall 76.92 % (40/52) patients with positive axillary metastasis were identified peri-operatively using combination of axillary ultrasound, cytology and sentinel lymph node biopsy.